2001
DOI: 10.1159/000046191
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Partitioning of Three Human Forearm Muscles

Abstract: Anatomical partitioning has been found in the human biceps brachii, extensor carpi radialis longus and flexor carpi radialis muscles. The purpose of this study was to determine if the human extensor carpi ulnaris, flexor carpi ulnaris and flexor digitorum profundus are anatomically partitioned. Evidence for or against anatomical partitioning was obtained by observation of the architectural and innervation characteristics of each of the investigated muscles. Twelve samples (11 were used for extensor carpi ulnar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 25 publications
5
52
1
1
Order By: Relevance
“…A study by Lim et al (1999) has showed that based on intramuscular innervation and vascular supply, FCU can be divided into humeral and an ulnar compartments, each with its own primary nerve branch. A similar report was given by Segal et al (2002) where they reported that, the nerve to the flexor carpi ulnaris clearly innervates two architectural partitions within the muscle. The innervation pattern to the flexor carpi ulnaris muscle is mathcing with muscle fiber architecture characteristics indicating consistent anatomical partitioning within the muscle.…”
Section: Case Reportsupporting
confidence: 69%
“…A study by Lim et al (1999) has showed that based on intramuscular innervation and vascular supply, FCU can be divided into humeral and an ulnar compartments, each with its own primary nerve branch. A similar report was given by Segal et al (2002) where they reported that, the nerve to the flexor carpi ulnaris clearly innervates two architectural partitions within the muscle. The innervation pattern to the flexor carpi ulnaris muscle is mathcing with muscle fiber architecture characteristics indicating consistent anatomical partitioning within the muscle.…”
Section: Case Reportsupporting
confidence: 69%
“…Anatomically, the innervation of some regions within the muscle is variable, with 2 primary nerve branches innervating a number of regions (Bhadra et al 1999;Segal et al 2002;Sunderland 1945). Distinct fascicular boundaries between muscle fibers inserting onto each of the 4 tendons are also difficult to identify.…”
Section: Comparison Of the Functional Organization Of The Human And Mmentioning
confidence: 99%
“…Third, studies of MU physiology have excluded data from recording sites where MUs were active during movement of more than one finger, potentially confining the data to highly selective regions of the muscle (Kilbreath and Gandevia 1994;Kilbreath et al 2002). Fourth, and finally, recent anatomical studies suggest that although the human FDP has some features of a subdivided muscle, it does not contain 4 distinct anatomical compartments (Bhadra et al 1999;Segal et al 2002). Taken together, these considerations raise the possibility that FDP might not be organized into 4 completely separate functional subdivisions.…”
Section: Introductionmentioning
confidence: 96%
“…Pertinent to this concept is that these segments have unique anatomical or fascicular arrangement (Segal et al, 2002;Wickham and Brown, 1998;Woodley and Mercer, 2005). Anatomical studies, texts and reviews have described three uniquely oriented segments within gluteus medius (GMed) (Al-Hayani, 2009;Flack et al, 2011;Gottschalk et al, 1989;Palastanga et al, 1989) and two within gluteus minimus (GMin) (Al-Hayani, 2009;Beck et al, 2000;Flack et al, 2011;Standring et al, 2005), supporting previous notions of functional differentiation within these muscles (Beck et al, 2000;Gottschalk et al, 1989;Grimaldi et al, 2009b;Soderberg and Dostal, 1978).…”
Section: Introductionmentioning
confidence: 99%